Discovery of heterocyclic substituted dihydropyrazoles as potent anticancer agents. (15th September 2021) - Chen, Chuan-Huizi; Jiang, Yuan; Wu, Runfang; Tang, Yanling; Wan, Chunping; Gao, Hui; Mao, Zewei
Graphical abstract: Abstract: In this work, a series of novel heterocyclic substituted dihydropyrazole derivatives have been prepared, and in vitro anticancer activity against a panel of human tumor cell lines by SRB were evaluated. The results indicated that piperazine substituted dihydropyrazole derivatives exhibited superior anticancer activity than that of other compounds. Especially, compounds 4g, 4h, 4l, 4m, 4o, 6g, 6j and 6l showed potent antitumor activity. Further mechanism study demonstrated that compound 4o could induce G2/M arrest in HCC1806 cell and p21 accumulation significantly.